2007
DOI: 10.1128/cvi.00420-06
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Enzyme-Linked Immunosorbent Assays Based on Crude and Recombinant Leishmanial Antigens for Serodiagnosis of Symptomatic and Asymptomatic Leishmania infantum Visceral Infections in Dogs

Abstract: The diagnosis of visceral leishmaniasis remains difficult in rural areas where the disease is endemic, and serologic methods still need assessment, as they are not very sensitive for the detection of asymptomatic infectious dogs. Here we present data on the development of enzyme-linked immunosorbent assay (ELISA)-based methods for the detection of antibodies against recombinant leishmanial antigens (namely, the recombinant K26 [rK26] and rK39 antigens from Leishmania infantum and the rA2 protein from Leishmani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
127
1
13

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(156 citation statements)
references
References 32 publications
15
127
1
13
Order By: Relevance
“…Porrozzi et al (2007) showed that ELISA based on crude antigens shown minor percentage (30%) for asymptomatic dogs than that ELISA based on recombinant leishmanial antigens rA2 (88%); rK39 and rK26 (66%). Thus, many efforts have been done to development more sensitive, specific and rapid tests to detection of CVL helping in epidemiology and to control the disease (ZIJLSTRA et al, 2001;ATTAR et al, 2001;MOHEBALI et al, 2004;AKHOUNDI et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Porrozzi et al (2007) showed that ELISA based on crude antigens shown minor percentage (30%) for asymptomatic dogs than that ELISA based on recombinant leishmanial antigens rA2 (88%); rK39 and rK26 (66%). Thus, many efforts have been done to development more sensitive, specific and rapid tests to detection of CVL helping in epidemiology and to control the disease (ZIJLSTRA et al, 2001;ATTAR et al, 2001;MOHEBALI et al, 2004;AKHOUNDI et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Additional investigation with symptomatic and asymptomatic dogs, done by parasitological tests, may provide further information for a better understanding of these results. Porrozzi et al (2007) showed that serologic tests using the recombinant protein rK39 and rK26 (both from L. infantum) were more efficient to identify symptomatic dogs while rA2 (from Leishmania donovani) seem to be effective for the serodiagnosis of asymptomatic dogs with the disease. Interestingly, only two of the 29 Leishmune  -vaccinated animals were seropositive by A2_ELISA, and showed ELISA levels near the cut-off point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This report from Brazil provided a comparison of ELISA using L. infantum rK26 and rK39 antigens and the L. donovani rA2 protein, as well as ELISA with crude soluble antigen (CSA), indicating a high sensitivity for rK26 and rK39 in the detection of symptomatic dogs (94% and 100%, respectively), followed by CSA (88%) and rA2 (70%). Conversely, rA2 was reported to be more sensitive for asymptomatic dogs (88%) than rK39 and rK26 (both 66%) and CSA (30%) (9) .…”
Section: Cross-reactionmentioning
confidence: 99%
“…Therefore, there is a need to develop a more rapid and simple assay for the diagnosis of VL (9) . Because the elimination of infected dogs is an important mean for controlling the transmission of VL, an ideal diagnostic test for VL in dogs would have to be inexpensive and simple, in addition to being specifi c and sensitive (9) .…”
mentioning
confidence: 99%